2021
DOI: 10.3390/ma14112955
|View full text |Cite
|
Sign up to set email alerts
|

How Can the Introduction of Zr4+ Ions into TiO2 Nanomaterial Impact the DSSC Photoconversion Efficiency? A Comprehensive Theoretical and Experimental Consideration

Abstract: A series of pure and doped TiO2 nanomaterials with different Zr4+ ions content have been synthesized by the simple sol-gel method. Both types of materials (nanopowders and nanofilms scratched off of the working electrode’s surface) have been characterized in detail by XRD, TEM, and Raman techniques. Inserting dopant ions into the TiO2 structure has resulted in inhibition of crystal growth and prevention of phase transformation. The role of Zr4+ ions in this process was explained by performing computer simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 94 publications
0
1
0
Order By: Relevance
“…Krishnapriya et al, investigated the effect of cobalt doping on the photoanode of a DSSC and recorded a power conversion efficiency of 6.86 % [13]. Research by Bartkowiat et al recorded an improved conversion efficiency of 8.63 % with a zirconium doped photoanode [14].…”
Section: Components Of Dsscmentioning
confidence: 99%
“…Krishnapriya et al, investigated the effect of cobalt doping on the photoanode of a DSSC and recorded a power conversion efficiency of 6.86 % [13]. Research by Bartkowiat et al recorded an improved conversion efficiency of 8.63 % with a zirconium doped photoanode [14].…”
Section: Components Of Dsscmentioning
confidence: 99%
“…The results showed that the Mn-doped TiO 2 has the highest benzene decomposition efficiency (~58%) in the range of investigated materials. Several studies worked on photocatalytic enhancement by doping other metals were also carried out [13][14][15][16][17][18][19][20][21]. However, the results were limited because the band gap was sufficiently large (E g > 3.0 eV) and the surface area was relatively low (<100 m 2 /g) [13][14][15][16] due to using the sol-gel method combined with high-temperature heating (>500 • C).…”
Section: Introductionmentioning
confidence: 99%